The political influence on the enforcement of international arbitral awards in Yemen - Bawazir, Omar Saleh Abdullah (Future Academy, 2018)
The judges are often frustrated of political interference which hindered the enforcement of the international arbitral award (IAA) or receiving threats from some parties to the conflict in case of compulsory attendance before the court. The executive interferes with the judicial affairs so the political intervention in the judiciary is the most element challenges the enforcement of (IAA). This study employed a doctrinal approach. Legal research method by applying data is collected through the library. As well, collect data through face to face semi-structured interview through the purposive sampling of choosing expert persons. The data are analysed by using the content analysis method. This study aims the legislator to make stricter laws to evade the political interference in the judiciary as well as aware the investors of the corrupt system in Yemen which the government has to fight if willing to enhance the arbitration system and attract the foreign direct investment. It has found some cases of arbitrary dismissal against judges because of judgments not in favour of the government. The judicial system can be considered as a branch of the executive body so the enforcement of IAA will fail in case the debtor party has any relationship with politicians.